INS GENE MUTATION IN NEONATAL DIABETES MELLITUS - Bing, Felicia Lee Yiik; Abdullah, Raja Aimee Raja; Hen, Moey Lip; Mustafa, Norlaila (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Neonatal diabetes mellitus (NDM) is a rare disorder with estimated prevalence of 1:90000 to 1:160000 live births. They usually present with persistent hyperglycemia within the first 6 months of life and some may persist up to 12 months of life. Approximately 80% of NDM patients have genetic mutation and more than 20 genes have been identified. Amongst these, KCNJ11 and ABCC8 genotype have been the most common cause of NDM accounting for 38.2%. INS gene mutation is also a known cause of NDM manifesting as damage to the pancreatic beta cells. Studies have shown that heterozygous autosomal dominant mutation is the 2nd most common cause of NDM. The average age for diagnosis in INS gene mutation NDM patients are 10 weeks old and 30% of them presented with DKA. INS gene mutation causes misfolding of the insulin protein which leads to the damage of the beta cells therefore the treatment of choice is insulin therapy. They usually present with low birth weight resulting from IUGR. INS gene mutation is known to cause both Transient Neonatal Diabetes Mellitus (TNDM) and Permanent Neonatal Diabetes Mellitus (PNDM) of which PNDM is more common and accounts for 20% of NDM. Here we present 2 different patients with homozygous mutations of INS gene; for which we want to emphasize the importance of genetic testing in diagnosing different types of NDM and its role in management.